A renaissance city hall - Walters, Dan (My University, 1908)
Introduction: Specifications for the erection and completion of a new City Hall for the city of [blank], [blank], after the drawings made for the same by Dan Walters, Student in the Architecture Course, Class of 1908, of the Kansas State Agricultural college, at Manhattan, Kansas, June 1, 1908.
Citation: Walters, Dan. A renaissance city hall. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Architecture; Blueprints; Construction; Design; Renaissance; Graduating theses; Senior theses; Theses